A Study of Cusp Base Areas in the Maxillary Permanent Molars of American Whites - Dustin P. Dinh; Edward F. Harris (Dental Anthropology Association, 2005)
The focus of this descriptive study was to explore the patterns of variation of base crown areas for the four major cusps on the maxillary first and second permanent molars in a cohort of contemporary North American whites of western European descent. A computer-assisted photogrammetric method was used to measure two-dimensional areas of the cusps. Ranking of mean cusp size was the same for M1 and M2, namely protocone > paracone > metacone > hypocone. In concert with field theory, size decreased while variability (CV) increased across this same sequence. Overall area of M1 (97 mm2) is 13% larger than M2 (86 mm2) in this sample. Most cusps exhibited significant sexual dimorphism, with greater differences for the distal cusps within a tooth and from M1 to M2. Intercorrelations of cusp areas were notably low (r2 < 15%) both within and between M1 and M2, suggesting considerable independence in formative rates of each cusp and low morphological integration of these constituents of the occlusal table. Limited comparative material in the literature suggests that cusp areas may valuably extend the quantitative comparisons for genetic and biological studies beyond conventional tooth crown width and length.